THE STATE OF COAGULATION, ANTICOAGULANT AND FIBRINOLITIC PARTS OF THE HEMOSTASIS SYSTEM IN BURN SHOCK - Yunusov Oybek Turaevich; Yunusova Guzal Fayzullayevna; Saydullaev Zayniddin Yakhshiboyevich (Scholar Express Journals, 2023)
The problem of burns is still one of the most urgent and difficult in modern medicine. First of all, it is connected with a significant spread of burns among the population, in connection with what it without exaggeration can be called a modern traumatic epidemic of densely populated cities and industrialized countries, which is caused by the continuing high level of this type of damage, the severity of its medical and social consequences
Keywords: damage; modern; connection; significant